Factors of Professional Activity of Educators in Pedagogical Practice - Vesna Kravarusić (International Journal of Cognitive Research in Science, Engineering and Education, 2021)
The indisputable importance of early learning as well as the accepted documents of international organizations dealing with education have an impact on educational policy in the Republic of Serbia. Systemic solutions support the professional progress of educators/preschool teachers. Clearly limited and publicly recognizable areas of practice, accumulated fund of knowledge acquired through education, experience, which is expanded and deepened by continuous improvement and exchange with the environment; independent and/or cooperative decisions on timely and correct actions; meeting internal and external standards (self / control); ethics in personal and professional life are characterized by professional/competent actions of educators. Factors that modulate the level of competence of educators are the status of society, the immediate social context, the quality of the study program, professional environment, continuous professional development, pedagogical practice, personal characteristics of educators, job satisfaction and private life. The paper critically examines the key elements of the structure of factors in the Republic of Serbia in order to put light on weak points and their improvement. The research of a set of macrosystemic and subsystemic factors points out to the necessity of restructuring, improvement of the quality of selection, basic education of educators, interventions in the offer of trainings in accordance with the real needs of educators. Ensuring an effective, respectful climate in the preschool institution is necessary for microsystem changes. Pedagogical implications are contained in the creation of conditions for the development of participatory relations, critical observation, but also the emancipation and independence of professionally accomplished educators.